Pajajaran dan Siliwangi dalam Lirik Tembang Sunda - Muhsin, Mumuh - (PANGGUNG, 2012)
ABSTRACTÃ‚Â History and literature are two of the many ways to describe the reality. These two ways have a difference extremely. History must be tightly based on fact, while literature is fictional and imagina- tive. However, between these two extreme points there is a slice. Its means that in history there is in certain limits an element of imagination and in literature there is an element of fact although just a name. Therefore, the reality of history can be used as a raw material of literature. In turn, therefore literature can critically be used as a source of history. In Tatar Sunda there are a number of literary works, especially in the form of lyrics Tembang Sunda, which the material is taken from historical facts. The name most widely used materials of lyrics are Pajajaran and Siliwangi. These two names refer to the golden age of the Sundanese throughout its history.Ã‚Â Keywords: Pajajaran, Siliwangi, rumpaka, Tembang Sunda, history.Ã‚Â Ã‚Â